2016
DOI: 10.1186/s12889-016-3177-8
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour change intervention for smokeless tobacco cessation: its development, feasibility and fidelity testing in Pakistan and in the UK

Abstract: BackgroundPeople of South Asian-origin are responsible for more than three-quarters of all the smokeless tobacco (SLT) consumption worldwide; yet there is little evidence on the effect of SLT cessation interventions in this population. South Asians use highly addictive and hazardous SLT products that have a strong socio-cultural dimension. We designed a bespoke behaviour change intervention (BCI) to support South Asians in quitting SLT and then evaluated its feasibility in Pakistan and in the UK.MethodsWe cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…In a recent survey of SLT consumers in Bangladesh and Pakistan (Azam et al, 2016;Siddiqi et al, 2016), the respondents indicated that their decisions to begin SLT use were influenced by peer pressure, family acceptance, easy access, low price, lack of regulation, wide cultural acceptance, curiosity, and hospitality. Among drivers in our study with a low SES who were unable to afford chewing gum, SLT served as a cost-effective, albeit addictive and alternative option for maintaining alertness during long duty hours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent survey of SLT consumers in Bangladesh and Pakistan (Azam et al, 2016;Siddiqi et al, 2016), the respondents indicated that their decisions to begin SLT use were influenced by peer pressure, family acceptance, easy access, low price, lack of regulation, wide cultural acceptance, curiosity, and hospitality. Among drivers in our study with a low SES who were unable to afford chewing gum, SLT served as a cost-effective, albeit addictive and alternative option for maintaining alertness during long duty hours.…”
Section: Discussionmentioning
confidence: 99%
“…However, they resumed use after experiencing strong withdrawal symptoms and because of a perceived occupational dependence on SLT. A similar study of factors related to behavioral interventions aimed at SLT cessation in Pakistan and the UK reported that 33 to 63% of SLT consumers were attempting to cease use of these addictive products but were unsuccessful because of peer pressure, isolation, and inconsistent motivation (Siddiqi et al, 2016). Similarly, as evident (Table 4 and 5) SLT consumption is 3-fold related to extra-long duty hours (>16), which alone is significant in univariate analysis; whereas in the presence of reduced (or No) influence by family or community environment, it might no longer remain significant as seen in multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most ST products contain a high nicotine concentration [ 4 ] and regular users show strong dependency [ 59 , 60 ]. Compared to smoking cessation, the evidence for ST cessation is limited and complicated by ST heterogeneity [ 61 ]. A Cochrane review [ 62 ], while concluding that pharmacotherapies and behavioural support may help ST users to quit, did not include any South Asian studies.…”
Section: Methodsmentioning
confidence: 99%
“…The latter findings were replicated in a multi-centre cohort study across South Asia [ 65 ]. A feasibility study found a culturally appropriate behaviour change intervention was acceptable to ST users in Pakistan and the UK [ 61 ]. One Indian RCT observed no difference in quit rates at 12 weeks (varenicline vs. placebo) [ 66 ], and a second showed a small effect of a community outreach intervention on abstinence at 6 months [ 67 ].…”
Section: Methodsmentioning
confidence: 99%